THE ROLE OF GENDER IN THE RELATIONSHIP BETWEEN PRE-SERVICE ENGLISH TEACHERS’ LEARNING INTERACTION AND ENGLISH ACADEMIC ACHIEVEMENT DURING DISTANCE LEARNING (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
A classroom is one of the core aspects of education in which students communicate with theirteachers, peers, and learning resources. As the COVID-19 pandemic triggers, several countriesworldwide have temporarily shut down their schools and switched from traditional education to adistance learning environment, on the one side, to reduce this pandemic in human societies and, onthe other, to ensure that learning is continuous. Inevitably this situation affects the transition in theIndonesian education system towards distance learning. Several research finds specific significantdistance learning considerations. However, preliminary research tends to reveal the importance oflearning interaction, specifically for pre-service English teachers. Thus, this research explores thediscrepancy which highlights the status of gender in the relationship between pre-service Englishteachers' learning interaction and English academic achievement during distance learning inIndonesia. We carried out a qualitative analysis to test the research model statistically. A surveywas used to accomplish the current research. The critical focus of the research was on a group ofpre-service English teachers consisting of 34 people. Data were received online from a Googleform. The instrument was an online survey of 8 statements, all closed statements. The findingssuggested a direct influence on English academic achievement through pre-service English teachers'learning interactions, although the impact could be moderate. The findings also revealed that maleswere more affecting than females in affecting the relationship between learning interaction andEnglish academic achievement during distance learning.